eHealth Literacy: Patient Engagement in Identifying Strategies to Encourage Use of Patient Portals Among Older Adults. - Price-Haywood, Eboni G.; Harden-Barrios, Jewel; Ulep, Robin; Luo, Qingyang (Population Health Management, 2017)
Innovations in chronic disease management are growing rapidly as advancements in technology broaden the scope of tools. Older adults are less likely to be willing or able to use patient portals or smartphone apps for health-related tasks. The authors conducted a cross-sectional survey of older adults (ages ≥50) with hypertension or diabetes to examine relationships between portal usage, interest in health-tracking tools, and eHealth literacy, and to solicit practical solutions to encourage technology adoption. Among 247 patients surveyed in a large integrated delivery health system between August 2015 and January 2016, eHealth literacy was positively associated with portal usage (OR [95% CI]: 1.3 [1.2-1.5]) and interest in health-tracking tools (1.2 [1.1-1.3]). Portal users compared to nonusers ( N = 137 vs.110) had higher rates of interest in using websites/smartphone apps to track blood pressure (55% vs. 36%), weight (53% vs. 35%), exercise (53% vs. 32%), or medication (46% vs 33%, all P < 0.05). Portal users noted cumbersome processes for accessing portals and variations in provider availability for online scheduling and response times to messages. Portal nonusers expressed concerns about data security, lack of personalization, and limited perceived value of using portals. Both groups noted the importance of computer literacy and technical support. Patient stakeholders recommended marketing initiatives that capture patient stories demonstrating real-life applications of what patients can do with digital technology, how to use it, and why it may be useful. Health systems also must screen for eHealth literacy, provide training, promote proxy users, and institute quality assurance that ensures patients' experiences will not vary across the system.